Impelementation of Problem Based Learning with Electronic Media on Student Learning Outcomes in Indonesia's - Philippines International Class - Nuris Fattahillah; Slamet Hariyadi (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
The curriculum in Philippines different with the curriculum in Indonesia. This make the learning process and the problems faced by students in Indonesia and Philippines different. One of the problems experienced by students is caused by the lack of variation in strategies in the teaching and learning process. The instructional model used by the teacher is to upgrade student learning outcomes, especially on high-level cognitive, in this research especially problem solving abilities. Instructional method used by researchers is Problem Based Learning (PBL) with a pretest posttest design. Data of this research obtained quantitatively and using the mean before and after the test. This study used control class and experimental class on material cells to organism. The results show that the experimental class has a higher average value of 88.6 compared to the control class, 81.9. These results indicate that PBL successfully increases learning activities and students can follow the learning model using PBL.